Triterpenoids from Chios Mastiha Resin Against MASLD—A Molecular Docking Survey - Nataša Milošević; Maja Milanović; Milica Medić Stojanoska; Varomyalin Tipmanee; Ilias Smyrnioudis; George V. Dedoussis; Nataša Milić (Current Issues in Molecular Biology)
Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease without an approved pharmacological approach for its prevention/treatment. Based on the modified Delphi process, NAFLD was redefined as metabolic dysfunction-associated steatotic liver disease (MASLD) to highlight the metabolic aspect of liver pathogenesis. Chios mastiha (Pistacia lentiscus var. Chia, Anacardiaceae) resin demonstrated promising results in MASLD treatment. In this paper, molecular docking was applied to test 16 compounds from Chios mastiha as potential ligands for the receptors GR, LXRα, LXRβ, PPARα PPARγ, MC4R, AMPK, and VEGFR2, whose up- and down-regulation interfere with MASLD development and progression. The observed compounds had moderate and high affinity for LXR, GR, MC4R, and PPARγ in comparison to proven ligands, while their affinity for PPARα, AMPK, and VEGFR was less pronounced. The combination of active compounds from Chios mastiha rather than a single molecule may have a superior ability to control the intertwined MASLD metabolic pathways.